Evaluation of the reasons for failure in teeth with vital amputation treatment - Yildiz, Semsettin; Dogan, M. Sinan; Dogan, Mehmet Emin (Bmc, 2023)
AimThis study aims to evaluate the primary teeth undergoing amputation due to dental caries or trauma clinically and radiologically.Material and methodsThe amputation treatment of 90 primary teeth of 58 patients (Female: 20, Male: 38) aged 4-11 years was evaluated clinically and radiologically. Calcium Hydroxide was used for amputation in this study. Composite or amalgam was preferred as filling material in the same session of the patients. Clinical/radiological (Periapical/Panoramic X-ray) examination was performed on the teeth that were unsuccessful in treatment, on the day of the patient's complaint, and at the end of 1 year in the others.ResultsAccording to the clinical and radiological findings of the patients, 14.4% of the boys and 12.3% of the girls were unsuccessful. Amputation in male was a need in the 6-7 age group with a rate of 44.6% at most. Amputation in females was a need in the 8-9 age group with a rate of 52% at most.ConclusionSuccess in amputation treatment depends on the tooth, the dentist, and the dental material applied.
Keywords: Deciduous tooth; Vital amputation; Calcium hydroxide